The first human fossil from the Ruidera site (Castilla-La Mancha, Spain): A partial parietal and its implications for Middle Pleistocene hominin variability in Southern Europe - D. García-Martínez; C. Buenestado Ruíz; S. Díaz Pérez; M. Bastir; L. Bermejo Albarrán; I. Campaña; O. Cambra-Moo; G. Cifuentes-Alcobendas; M. del Val; M. Duval; M.D. D'Angelo del Campo; B. Fernández Cascón; et al. (Journal of Human Evolution, 2026)

A New Tailored Analytical Method for Estimating Breach Parameters and Peak Discharge in Earthen Ponds - Mónica Delgado; Francisco-Javier Sánchez-Romero; Modesto Pérez-Sánchez; Helena M. Ramos (Water Resources Management, 2026)

Hybrid regulation of non-conventional water sources powered by renewable energy: advancing circular water management for coastal cities resilience - Miguel-Ángel Bofill; Francisco-Javier Sánchez-Romero; Francisco A. Zapata; Helena M. Ramos; Modesto Pérez-Sánchez (Water Research, 2025)

A Comprehensive Database of Expert‐Curated Occurrences for the Genus Carex L. (Cyperaceae) - María Sanz‐Arnal; Pablo García‐Moro; Carmen Benítez‐Benítez; Marina Coca‐de‐la‐Iglesia; Angélica Gallego‐Narbón; Consolación Barciela; Fabrizio Bartolucci; Prabin Bhandari; Matthew Bradley; Asunción Cano; Antoine Derouaux; Sabina Donadío; et al. (Global Ecology and Biogeography, 2025)
Motivation Geographic occurrences are essential for biodiversity studies, but publicly available repositories like GBIF often contain errors and biases, especially for taxonomically complex groups like Carex L. (Cyperaceae). This work provides an expert‐curated global dataset of occurrences compiled from different sources to enhance data accuracy and usability. The final dataset includes 384,067 occurrences of 1790 Carex species. Main Types of Variables Contained The dataset includes species occurrence records with geographic coordinates, taxonomic identifications, and curation flags (e.g., introduced, erroneous records). Spatial Location and Grain The dataset covers a global scale, using the WGS84 projection. Spatial resolution is standardised to a minimum of three decimal degrees (~1 km, if possible). Time Period and Grain Online records span from 1950 to 2020, but some manually georeferenced records are earlier (1850). There is also fieldwork data after 2020, specifically up to 2023. Major Taxa and Level of Measurement Cyperaceae: Carex . Most records have species‐level identification, and some of them are identified at subspecies or variety levels. Software Format Data are supplied as comma‐separated values files with UTF‐8 encoding.

Test-Retest Reliability of Single Leg Jump Performance Using the Drift Protocol in Division I Baseball Pitchers - Amy M. Bergquist; Modesto A. Lebron; L. Colby Mangum; Jeffrey R. Stout; David H. Fukuda (Journal of Science in Sport and Exercise, 2025)

Assessing the Impact of Hydraulic Control Structures on Hydrodynamic Modelling in Shallow Waters - Alfonso Arrieta-Pastrana; Edwin A. Martínez-Padilla; Modesto Pérez-Sánchez; Oscar E. Coronado-Hernández; Helena M. Ramos (Journal of Marine Science and Engineering, 2025)
Currently, hydrodynamic models for bay and estuarine systems involve many parameters that require proper calibration to design coastal structures effectively. However, in coastal regions with limited data availability, the implementation of such models becomes challenging. This research introduces a simplified hydrodynamic methodology designed to analyse the impact of hydraulic control structures in shallow waters. This approach offers a computationally efficient alternative that allows engineers to rapidly evaluate the impact of horizontal and vertical constrictions in shallow waters experiencing wave propagation. A practical application is demonstrated in a one-dimensional channel with a length of 200,000 m and an average depth of 5 m. The only parameter required for calibration in the proposed methodology is bed friction. The three analysed scenarios—longitudinal constriction, plan-view constriction, and the influence of bed friction—demonstrate the model’s sensitivity to these variations, highlighting its reliability as a decision-making tool for coastal engineering projects. Moreover, the comparison of the proposed hydrodynamic simulation methodology at the stabilised tidal inlet structure in Cartagena de Indias, Colombia, demonstrated its ability to reproduce observed water levels accurately, reinforcing its reliability and potential for broader application.

Hunting Iberian ibex: from a threat factor to a conservation tool - Jesús M. Pérez; Fabiola Mesa-Pérez; María J. Fernández-Muñoz; José E. Granados; Paulino Fandos; Ramón C. Soriguer; Pelayo Acevedo; Pablo Refoyo; Enrique Barreñada; Juan Carlos Peral; Alberto Fernández-Arias; José A. Martínez; et al. (European Journal of Wildlife Research, 2025)
In this study we have compiled the information from official databases about Iberian ibex, Capra pyrenaica , hunting yields, hunting trophies and hunting licenses in the Spanish regions where the species is present and hunted. Such quotas showed an increasing trend between 2005–2021 and, on average, during this period, ≈ 6400 animals were yearly harvested. Despite this number decreased in 2019 and 2020 (in this last year, mainly due to the lock down caused by the COVID pandemia), the annual quota raised, reaching over 12,000 ibexes in 2021. The number of trophies increased since the 1970s and peaked in the period 2001–2005, and then declined during the period 2006–2020. At national level, the number of hunting licenses decreased from 2006 to 2021 by a 36.5%. The regional average hunting yield was significantly correlated with a regional-based ibex abundance estimation. The current situation of continued population increase together with the trophy reduction might suggest that the overall population is exceeding the carrying capacity. In this context, if hunting activity was one of the main factors involved in local extinction of the species, currently it should be considered a tool for sustainable managing of ibex populations in an scenario of increasing demographic trends and generalized absence of predators.

What we know and do not know about the invasive Asian clam Corbicula fluminea - Vanessa Modesto; Martina Ilarri; Anna M. Labecka; Noé Ferreira-Rodríguez; Neil E. Coughlan; Xiongjun Liu; Ronaldo Sousa (Hydrobiologia, 2025)

Phylogenetic characterization of Bifidobacterium kimbladii sp. nov., a novel species from the honey stomach of the honeybee Apis mellifera - M. Modesto; D. Scarafile; A. Vásquez; R. Pukall; M. Neumann-Schaal; S. Pascarelli; B. Sgorbati; M. Ancora; C. Cammà; P. Mattarelli; T.C. Olofsson (Systematic and Applied Microbiology, 2025)

A new optimized procedure for circular WasteWater sustainability: Coastal cities supporting agricultural rural communities - Modesto Pérez-Sánchez; Francisco-Javier Sánchez-Romero; Francisco A. Zapata; Helena M. Ramos (Journal of Water Process Engineering, 2024)

Smart feasibility optimization of hybrid renewable water supply systems by digital twin technologies: A multicriteria approach applied to isolated cities - Miguel Tavares; Modesto Pérez-Sánchez; Armando Carravetta; Oscar E. Coronado-Hernández; P. Amparo López-Jiménez; Helena M. Ramos (Sustainable Cities and Society, 2024)

Anatomy of the olfactory system and potential role for chemical communication in the sound‐producing Lusitanian toadfish, Halobatrachus didactylus - Teresa Modesto; Beatriz Neves Gregório; Gonçalo Marcelino; Nathalie Marquet; Rita A. Costa; Pedro M. Guerreiro; Zélia Velez; Peter C. Hubbard (Journal of Fish Biology, 2024)
The current study investigated the structure and function of the olfactory system of the Lusitanian toadfish, Halobatrachus didactylus , using histology and electrophysiology (electro‐olfactogram [EOG]), respectively. The olfactory system consists of a digitated anterior peduncle, of unknown function, containing the inhalant nostril. This then leads to a U‐shaped olfactory chamber with the olfactory epithelium—identified by G αolf ‐immunoreactivity—on the ventral surface. A large lacrimal sac is connected to this tube and is likely involved in generating water movement through the olfactory chamber (this species is largely sedentary). The exhalent nostril lies by the eye and is preceded by a bicuspid valve to ensure one‐way flow of water. As do other teleosts, H. didactylus had olfactory sensitivity to amino acids and bile acids. Large‐amplitude EOG responses were evoked by fluid from the anterior and posterior testicular accessory glands, and bile and intestinal fluids. Anterior gland and intestinal fluids from reproductive males were significantly more potent than those from non‐reproductive males. Male urine and skin mucus proved to be the least potent body fluids tested. These results suggest that chemical communication—as well as acoustic communication—may be important in the reproduction of this species and that this may be mediated by the accessory glands and intestinal fluid.

Dynamic Effects of a Regulating Valve in the Assessment of Water Leakages in Single Pipelines - Oscar E. Coronado-Hernández; Modesto Pérez-Sánchez; Alfonso Arrieta-Pastrana; Vicente S. Fuertes-Miquel; Jairo R. Coronado-Hernández; Edgar Quiñones-Bolaños; Helena M. Ramos (Water Resources Management, 2024)
Water losses in water distribution systems are typically analysed using extended period simulations, where its numerical resolution is commonly achieved using the gradient method. These models assume that adjustments to regulating valves occur, either manually or automatically, over an extended period of time, then the system inertia can be neglected. This research introduces the development of a rigid water column model for analysing water leakages in single pipelines, which can be employed to account for regulation valve adjustments in shorter time periods, thereby providing greater accuracy when assessing water losses. The application to a case study is presented to analyse pressure variations and leakage flow patterns over 30, 60, and 180 s. A comparison between the extended period simulation and rigid water column model is presented in order to note the order of magnitude on leakages when the system inertia is not considered. The results confirm that is crucial for water utilities the consideration of inertial system to simulate adequately opening and closure manoeuvres in water distribution systems, since according to the case study the extended period simulation can overestimated or underestimated the total leakage volume in percentages of 37.1 and 55.2 $$%$$ % , respectively.

Exploring options for energy recovery from wastewater: Evaluation of hydropower potential in a sustainability framework - Rosa M. Llácer-Iglesias; P. Amparo López-Jiménez; Modesto Pérez-Sánchez (Sustainable Cities and Society, 2023)

Addressing inconsistencies in Cyperaceae and Juncaceae taxonomy: Comment on Brožová et al. (2022) - Tammy L. Elliott; Isabel Larridon; Russell L. Barrett; Jeremy J. Bruhl; Suzana M. Costa; Marcial Escudero; Andrew L. Hipp; Pedro Jiménez‐Mejías; Jan Kirschner; Modesto Luceño; José Ignacio Márquez-Corro; Santiago Martín-Bravo; et al. (Molecular Phylogenetics and Evolution, 2023)

Activated carbon production from industrial yeast residue to boost up circular bioeconomy - Helen R. Modesto; Sherlan G. Lemos; Mikaela S. dos Santos; Jenny S. Komatsu; Maraísa Gonçalves; Wagner A. Carvalho; Elma N. V. M. Carrilho; Geórgia Labuto (Environmental Science and Pollution Research, 2021)

Standard area diagram set for anthracnose severity on grapevine bunches and shoots - L. R. Modesto; D. R. M. Steiner; J. K. Menon; R. O. Nodari; L. J. Welter; A. L. da Silva (Australasian Plant Pathology, 2020)

Palatability of the Asian clam Corbicula fluminea (Müller 1774) in an invaded system - P. S. Castro; M. I. Ilarri; V. Modesto; C. Antunes; R. Sousa (Hydrobiologia, 2018)

Modified Affinity Laws in Hydraulic Machines towards the Best Efficiency Line - Modesto Pérez-Sánchez; P. Amparo López-Jiménez; Helena M. Ramos (Water Resources Management, 2018)

Association of a specific major histocompatibility complex class IIβ single nucleotide polymorphism with resistance to lactococcosis in rainbow trout, O ncorhynchus mykiss (Walbaum) - S Colussi; M Prearo; S A Bertuzzi; T Scanzio; S Peletto; L Favaro; P Modesto; M G Maniaci; G Ru; R Desiato; P L Acutis (Journal of Fish Diseases, 2015)
Major histocompatibility complex ( MHC ) loci encode glycoproteins that bind to foreign peptides and initiate immune responses through their interaction with T cells. MHC class II molecules are heterodimers consisting of α and β chains encoded by extremely variable genes; variation in exon 2 is responsible for the majority of observed polymorphisms, mostly concentrated in the codons specifying the peptide‐binding region. L actococcus garvieae is the causative agent of lactococcosis, a warm‐water bacterial infection pathogenic for cultured freshwater and marine fish. It causes considerable economic losses, limiting the profitability and development of fish industries in general and the intensive production of rainbow trout, O ncorhynchus mykiss (Walbaum), in particular. The disease is currently controlled with vaccines and antibiotics; however, vaccines have short‐term efficacy, and increasing concerns regarding antibiotic residues have called for alternative strategies. To explore the involvement of the MHC class II β‐1 domain as a candidate gene for resistance to lactococcosis, we exposed 400 rainbow trout to naturally contaminated water. One single nucleotide polymorphism ( SNP ) and one haplotype were associated with resistance ( P MHC class IIβ as a molecular marker in breeding rainbow trout resistant to lactococcosis.

Herbivores mediate different competitive and facilitative responses of native and invader populations of Brassica nigra - Ayub M. O. Oduor; Sharon Y. Strauss; Yedra García; Modesto Berbel Cascales; José M. Gómez (Ecology, 2013)
Differences in plant and herbivore community assemblages between exotic and native ranges may select for different levels of plant traits in invasive and native populations of plant species. Little is currently known of how herbivores may mediate competitive and facilitative interactions between invasive and native populations of plant species and their plant neighbors. Here, we conducted a common‐garden field experiment to test whether invasive and native populations of Brassica nigra differ in phenotypic expressions of growth (biomass and plant height) and reproductive (seed yield) traits under different plant neighbor treatments and ambient vs. reduced level of insect herbivore damage on the B. nigra plants. We found significant interactive effects of plant neighbor treatments, level of insect herbivore damage on B. nigra plants, and invasive status of B. nigra on the phenotypic trait expressions. Plant neighbor treatments had minimal effects on phenotypic trait expressions by invasive populations of B. nigra under either level of insect herbivore damage. In contrast, for native populations of B. nigra , ambient level of insect herbivore damage resulted in plant neighbors facilitating expression of the traits above, while reduced damage resulted in plant neighbors competitively suppressing trait expression. Our results suggest that insect herbivores and plant neighbors interactively shape expression of plant traits in native and exotic ranges of invasive plants. Such interactions could potentially lead to different selection pressures on traits that determine antiherbivore defenses and plant–plant interactions.

Fine mapping of QTLs for rice grain yield under drought reveals sub-QTLs conferring a response to variable drought severities - Shalabh Dixit; B. P. Mallikarjuna Swamy; Prashant Vikram; H. U. Ahmed; M. T. Sta Cruz; Modesto Amante; Dinesh Atri; Hei Leung; Arvind Kumar (Theoretical and Applied Genetics, 2012)

The last “pelycosaur”: a varanopid synapsid from the Pristerognathus Assemblage Zone, Middle Permian of South Africa - Sean P. Modesto; Roger M. H. Smith; Nicolás E. Campione; Robert R. Reisz (The Science of Nature, 2011)

Osteomyelitis in a Paleozoic reptile: ancient evidence for bacterial infection and its evolutionary significance - Robert R. Reisz; Diane M. Scott; Bruce R. Pynn; Sean P. Modesto (The Science of Nature, 2011)

Magnetic properties and Archeointensity of Earth’s magnetic field recovered from El Opeño, earliest funeral architecture known in Western Mesoamerica - Modesto Pineda Duran; Avto Goguitchaichvili; Juan Morales; Bertha Aguilar Reyes; Luis M. Alva Valdivia; Arturo Oliveros-Morales; Manuel Calvo-Rathert; Tomas Gonzalez Moran; Jasinto Robles-Camacho (Studia Geophysica et Geodaetica, 2010)

The effect of cropping systems and irrigation management on development of potato early blight - O. Modesto Olanya; C. Wayne Honeycutt; Robert P. Larkin; Timothy S. Griffin; Zhongqi He; John M. Halloran (Journal of General Plant Pathology, 2009)

Indinavir-Loaded pH-Sensitive Microparticles for Taste Masking: Toward Extemporaneous Pediatric Anti-HIV/AIDS Liquid Formulations with Improved Patient Compliance - Diego A. Chiappetta; Ángel M. Carcaboso; Carlos Bregni; Modesto Rubio; Guillermo Bramuglia; Alejandro Sosnik (AAPS PharmSciTech, 2009)

Combined effects of air and soil pollution by fluoride emissions on Tibouchina pulchra Cogn., at Cubatão, SE Brazil, and their relations with aluminium - M. Domingos; A. Klumpp; M.C.S. Rinaldi; I.F. Modesto; G. Klumpp; W.B.C. Delitti (Plant and Soil, 2003)

17α,20β,21‐Trihydroxy‐4‐pregnen‐3‐one: the probable maturation‐inducing steroid of the Lusitanian toadfish - T. Modesto; A. V. M. Canário (Journal of Fish Biology, 2002)
17,20β,21‐Trihydroxy‐4‐pregnen‐3‐one (17,20β,21‐P) was identified as the major metabolite of incubations of Lusitanian toadfish Halobatrachus didactylus ovarian follicles with [ 3 H]‐17hydroxyprogesterone. The potency of several steroids in inducing germinal vesicle breakdown of follicle‐enclosed oocytes of Lusitanian toadfish was systematically examined by using an in vitro germinal vesicle breakdown (GVBD) bioassay. 17,20β‐Dihydroxy‐4‐pregnen‐3‐one (17,20β‐P) and 17,20β,21‐P, two confirmed maturation‐inducing steroids (MIS) in teleosts, were the most potent in inducing GVBD with ED 50 s ranging between 9 and 271 nM. Structure‐activity relationships followed similar patterns to what has been observed in similar bioassays, i.e. a vital requirement for 17‐ and 20β‐hydroxyl groups in C21 steroids and a reduction in activity of 14 and 5–6%, respectively, for 5‐pregnene and 5β‐pregnanes compared to 4‐pregnenes. Corticosteroids, testosterone and 17β‐oestradiol were ineffective. Folliculated oocytes stimulated by pituitary homogenate produced 17,20β,21‐P from endogenous substrates in amounts one order of magnitude higher than 17,20β‐P. These results strongly support the hypothesis that 17,20β,21‐P is the likely MIS in this species.

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)